Upcycling Denim as an Eco-Friendly Fashion Solution - Kencana, Mega; Rahmanita, Nofi; Yurisman (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Upcycling clothing is a sustainable strategy that reduces fabric waste. We offer upcycle by transforming used consumer denim into new clothing, thereby enhancing its elegant aesthetic value. The choice of denim as the primary material for this study stems from an understanding of the detrimental effects of textile waste on the environment and the lack of sustainable fashion practices, particularly in terms of recycling. This again offers an opportunity to reduce textile waste, save resources, and encourage awareness of sustainability in fashion. The fashion industry, constantly producing new products every season, contributes to the existence of textile waste. Upcycling, a process that transforms old clothes or textile waste into fashion products with high artistic value, is one way to reduce the environmental impact of the fashion industry. The success of this study resulted in the creation of fashion products that not only enhance their artistic value but also contribute to the growth of the fashion industry's creative sector. The purpose of this applied research on the theme of upcycling is to present practical examples of upcycling from denim and patchwork materials, aiming to create sustainable designs by repurposing unused clothing. This applied research produces a fashion collection that is not only contemporary but also sustainable, consisting of two upcycled fashion products.